Mittelverknappung im Gesundheitswesen: Leistungsträger und Beitragsstabilität auf dem Prüfstand - Strohm, Theodor (Zeitschrift für evangelische Ethik, 1997)
The author examines the reasons of the rising expenditures in the Public-Health-System. He pointsout the different ways and strategies for solving this problern and tests out criterions for the radius and realistic capacity of solidarity and responsibility in an ethical perspective: Solidarity is not only a single matter of those, who are depending on solidarity of the society
Veröffentlicht von Gütersloher Verlagshaus 9. September 2014
Gesehen am 03.06.2024
Keywords: Gesundheitswesen; Sparprogramm; Deutschland